Depositories of the type material of the species Coccidophilus lozadaiGonzalez, 2012 (Insecta: Coleoptera: Coccinellidae) - Lozada, Pedro W. (2013)
6 paratypes of the species Coccidophilus lozadai Gonzalez, 2012, are deposited in the collection of Servicio Nacional de Sanidad Agraria (SENASA), Lima, Peru. The holotype and remaining paratypes are deposited in the Museo de Historia Natural (MUSM), Lima, Peru, and National Museum of Natural History (USNM), Washington, D.C., USA.